Statistical modelling of HIV/AIDS epidemics; Nigeria’s most needful statistical support for meeting the MDGs in HIV/AIDS intervention initiatives. (2006)
Since the first cases of AIDS were identified in the United State of America nearly two decades ago, researchers have made significant progress in understanding the epidemiology of HIV/AIDS Pandemic worldwide, with special attention to Sub-Saharan Africa. However, no particular attempt has been made to Model either the transmission dynamics or the trajectory of HIV/AIDS infection in Nigeria. In this paper, we review various methods adopted by Mathematicians and statisticians to Model HIV/AIDS epidemics. Their peculiar applicability and limitations with reference to Nigeria are discussed. We also discuss why Statistical Modeling of HIV/AIDS Epidemics is one of the most needed Statistical support for meeting the Millennium Development Goals (MDGs), particularly in Nigeria.